1995
DOI: 10.1182/blood.v86.2.651.bloodjournal862651
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine loops involving interferon-gamma and IP-10, a cytokine chemotactic for CD4+ lymphocytes: an explanation for the epidermotropism of cutaneous T-cell lymphoma? [see comments]

Abstract: Human interferon-gamma (IFN-gamma)-inducible protein 10 (IP-10), a C-X- C chemokine, is secreted by IFN-gamma-stimulated keratinocytes and is chemotactic for CD4+ lymphocytes. We therefore investigated its role in the epidermotropism of cutaneous T-cell lymphoma (CTCL) that is known to express IFN-gamma mRNA in the epidermis and is characterized by an indolent course with multiple relapses that remain confined to the skin for many years. By injecting purified recombinant (r) IP-10 we generated a polyclonal rab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(29 citation statements)
references
References 38 publications
1
27
0
1
Order By: Relevance
“…Note, however, that all studies to date have identified and visualized IP-10 as a downstream molecule induced by IFN-g directly or subsequent to IL-12 activity. Thus, Sarris et al (36) proposed that the interaction between IFN-g produced by lymphoma cells and IP-10 by keratinocytes was responsible for epidermotropism of CTCL cells. Based on the present study, where IP-10 clearly promotes strong IFN-g gene expression by antigen or polyclonally stimulated cells, we propose the existence of a positive amplification loop between IP-10 and IFN-g in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Note, however, that all studies to date have identified and visualized IP-10 as a downstream molecule induced by IFN-g directly or subsequent to IL-12 activity. Thus, Sarris et al (36) proposed that the interaction between IFN-g produced by lymphoma cells and IP-10 by keratinocytes was responsible for epidermotropism of CTCL cells. Based on the present study, where IP-10 clearly promotes strong IFN-g gene expression by antigen or polyclonally stimulated cells, we propose the existence of a positive amplification loop between IP-10 and IFN-g in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…IP-10 staining was diffuse and not localized to focal keratinocytes. It was similar in intensity and pattern to IP-10 staining in the epidermis of psoriasis (24) and mycosis fungoides (17,25,26). IP-10 is hypothesized to recruit and stimulate helper T cells.…”
Section: Discussionmentioning
confidence: 64%
“…CXCL10/IP-10 gene and protein expression is modulated by pro-inflammatory stimuli. Indeed, IFNγ is an inducer of the gene and protein expression of this chemokine by mononuclear cells [28], neutrophils [36,37], eosinophils [37,72], keratinocytes [28,31,32,34], fibroblasts [28], endothelial cells [28][29][30], pancreatic βcells [38,39], and animal astrocytes/microglia [33,35]. TNFα [37,[40][41][42][43][44][45][46], Interleukin (IL-1β) [37,38], as well as viral [33,48,49] and microbial products [37,47,[50][51][52], can also stimulate the production of IP-10.…”
Section: The Chemokine Cxcl10/ip-10mentioning
confidence: 99%
“…IP-10 is inducible by pro-inflammatory stimuli such as interferon-γ (IFN-γ) [28][29][30][31][32][33][34][35][36][37][38][39], tumor necrosis factor-α (TNF-α) [37,[40][41][42][43][44][45][46] viruses, and microbial products [33,37,[47][48][49][50][51][52], either directly or through NF-kB [48,49,[53][54][55][56]. It has been proposed that this chemokine is also involved in the recruitment and potentiation of T-helper 1 (Th1) responses [57][58][59].…”
Section: Introductionmentioning
confidence: 99%